Symbolism and stereotypes in the cultural depiction of Turning Red movie - Huda, Miftahul; Yustisia, Karlina Karadila; Winarsih, Anis Dwi (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2024)
This paper explores the cultural representation in Turning Red, focusing on the use of symbolism and stereotypes. Through an analysis of key motifs and visual elements in the film examines how the narrative reflects and challenges cultural identities, particularly those within the Asian diaspora. The study applies a qualitative content analysis methodology, identifying and interpreting symbols related to culture, tradition, and family dynamics. Key results reveal that the film uses the metaphor of transformation to represent the protagonist’s struggle with generational expectations while also highlighting stereotypes associated with Asian heritage. The analysis also shows how these symbols are both subverted and reinforced throughout the film, creating a complex portrayal of cultural identity. In conclusion, Turning Red presents a nuanced perspective on cultural representation, using symbolism and stereotypes to challenge and affirm cultural narratives, ultimately offering a deeper understanding of generational conflict and cultural belonging.